Performance pay and wage inequality - Thomas Lemieux; W. Bentley MacLeod; Daniel Parent (Institute for the Study of Labor (IZA), 2007)
We document that an increasing fraction of jobs in the U.S. labor market explicitly pay workers for their performance using bonuses, commissions, or piece-rates. We find that compensation in performance-pay jobs is more closely tied to both observed (by the econometrician) and unobserved productive characteristics of workers. Moreover, the growing incidence of performance-pay can explain 24 percent of the growth in the variance of male wages between the late 1970s and the early 1990s, and accounts for nearly all of the top-end growth in wage dispersion (above the 80th percentile).
Keywords: 330; Lohnstruktur; Arbeitsproduktivität; Grenznutzentheorie; Leistungsorientierte Vergütung; USA